Knowledge, attitude, and practices of cervical cancer prevention among female Nursingstudents at Thai Binh University of Medicine and Pharmacy (TẠP CHÍ Y DƯỢC THÁI BÌNH, 2024)
Objective: To describe the knowledge, attitude, and practices of cervical cancer prevention among female nursing students at Thai Binh University of Medicine and Pharmacy in the academic year 2022-2023.Method: A cross-sectional descriptive study was conducted with 302 female nursing students from the first to the third year in the academic year 2022-2023.Results: Nursing students’ knowledge of cervical cancer prevention was more than 80%. In which, general knowledge of cervical cancer and positive attitude towards cervical cancer of nursing students were 52,0% and 89.4%, respectively.Conclusion: There is a need for plans and communication programs to raise awareness among nursing students about cervical cancer, cervical cancer screening, and HPV vaccine, thereby contributing to cervical cancer prevention.